Historical Kyoto : - Plutschow, Herbert E. (Japan Times, 1983)
Kyoto is one of Japan's largest cities and the ... Nijo Castle - Floor plan map .... the palace itself can only be visited as part of a guided tour operated by the Imperial Household ... was completely renovated in 2014 and boasts numerous examples of historic art and applied arts ...